TRANSFORMING DIAGNOSTIC DATA ON THE INDIVIDUAL PSYCHOSOCIAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS WITH DELAYED MENTAL DEVELOPMENT INTO PEDAGOGICAL TASKS (European Journal of Interdisciplinary Research and Development, 2025)
This article explores the transformation of diagnostic data on the psychosocial development of primary school students with delayed mental development (DMD) into concrete pedagogical tasks. The study aims to create a practical model for applying diagnostic information in classroom activities to enhance the personal and social growth of each child. Diagnostic data were obtained through observation, play, interview, and testing methods. The findings reveal that converting diagnostic indicators into individualized pedagogical goals fosters the child’s self-regulation, communication skills, and learning motivation. The paper also proposes an algorithm for integrating psychosocial diagnostics into correctional and educational practice.